Pengaruh Employee Experience dan Employee Engagement Terhadap Life Satisfaction dengan Job Satisfaction Sebagai Intervening Variable di PT MCS - Nurkesuma, Nurkesuma; Djamil Mz, Masyudzulhak (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This research aims to analyze the influence of Employee Experience and Employee Engagement on Life Satisfaction with Job Satisfaction as an intervening variable for PT MCS employees. This research was conducted on 55 PT MCS employees, both permanent employees and contract employees as a saturated sample, using a survey method via a questionnaire distributed online. The data analysis method uses the Structural Equation Model-Partial Least Square (SEM-PLS). The research results show that there is a direct positive influence of Employee Experience and Employee Engagement on Life Satisfaction through Job Satisfaction as an intervening agent. This means that if there is high employee involvement and experience, it can be predicted that job satisfaction will also be high and have an impact on the life satisfaction felt by employees. Employee Experience and Employee Engagement directly and individually also have a positive influence on Job Satisfaction. This research found the results of a direct negative influence of Employee Engagement on Life Satisfaction. However, Employee Engagement has a positive effect if it is mediated by Job Satisfaction. This research also shows that the number of employees who are currently not involved (not engaged) in the company is much greater than the number of employees who are engaged. Apart from that, this research also shows that the majority of employees have ambiguous feelings regarding satisfaction with the Company. Only in the task aspect do employees show satisfaction.